Coase and the problem of social cost - vikramaditya, vibhu; block, walter (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
In the view of many, Coase (1960) overcame and supplanted Pigou (1932) in terms of the sophistication, and accuracy of the law and economic analysis of social cost. It is the task of the present paper to main that the same fate should befall Coase. We have through are paper tried to redefine the problem, showing in the process that the problem of social cost is the problem of violation of private property rights which in policy and judicial implementation becomes the problem of establishing the harm done, and holding the damaging party responsible for the violation.